Developing a Problem-Based Learning Approach to the Integration of Environmental and Occupational Health Topics into Medical School Curriculum. Issue 8 (August 2018) - Garg, Anisha; Mulloy, Karen B.
Abstract : Objectives: A pilot study incorporating environmental and occupational health (EOH) learning objectives into medical school curriculum using problem-based learning approach. Methods: One hundred eight-four Case Western Reserve University medical students participated in problem-based learning curriculum emphasizing EOH topics. Multiple choice (MCQ), short essay (SEQ), and summative short essay (SSEQ) questions assessed student knowledge. Two rating scale questions and one open-ended question determined student attitudes and confidence. Results: Eighty percent of students answered 10 of 12 MCQs correctly. Students scored 70% on three of four SEQs and averaged 95.2% and 88.5% on two final SSEQs demonstrating improvement in student knowledge. Students rated the importance of and confidence in EOH topics as 4.4 and 3.9, respectively. Conclusion: Problem-based learning facilitated inclusion of new EOH content in pre-clerkship curriculum leading to achievement of students' cognitive objectives, positive attitudes, and improved confidence in EOH topics.